A standard Kansei-based web design for Malaysian higher learning institutions - Punitha Turumugon (2018)
Emotions evidently play an important role in the entire human accomplishments as emotions aid in decision making, including Human-Computer Interaction (HCI). Emotion research in the field of HCI has only started recently and continuously evolving through the investigation and understanding of emotional effects. Thus, it forms an intelligent interaction between human and computer by responding effectively to the humans’ feelings. Emotional design generates remarkable user experiences for websites as the emotional experiences create an intense impression on our long-term memory. Recent scientific findings recommend emotional elements to be considered in designing websites as emotions influences one’s perception, conception and decision-making throughout the interaction with a website. A poorly designed user interface leads to bad user interaction while rising the users’ arousal and a displeasing user experience with a website elicits dissatisfaction emotion where consecutively results in avoidance and prevents revisit to the website. This proves the importance of emotional engagement in a website design. This research identified a standard Kansei-based web design guideline for Malaysian higher learning institutions using Kansei engineering method. 12 different design higher learning institution websites with 16 Kansei words were used to evaluate users’ feelings towards the selected websites and were analyzed to identify a standard Kansei-based web design guideline. Current Universiti Malaysia Sabah website was adapted based on the identified standard web design guideline and was evaluated with Geneva Emotion Wheel and Kansei Checklist. A total of 143 participants involved in the evaluation of users’ emotional experience towards the Kansei-based Universiti Malaysia Sabah website. The users’ emotional experience evaluation has proved that the adapted website does cultivate positive emotional engagement between users with the identification of users’ emotion model. The identified guideline with details design elements was successfully justified and can be used in design practices of Malaysian higher learning institutions’ website.